VALORES EN EDUCACIÓN AMBIENTAL PARA LA PREVENCIÓN DE DESASTRES - Talero de Husain, Elsa Leonor; Umaña, Gloria; Chaves, Gilma (Tecné, Episteme y Didaxis: TED, 1998)
The educational project on disaster prevention is an approximation towards a pedagogical strategy in significant learning, in values formation and concepts construction for the mountain system and the factors that affect the antropic steadystate equilibrium of the environment. The design centers on teachers, students and community values clarification in order to incorporate geological hazards on vulnerability and risk of disasters. The main objective of the study was to design a curricula and to develop the educational. Project on disasters prevention that improve knowledge of existing hazard condition and distributions, as well as attitudes and values towards disasters. The pedagogical .strategy tend, to minimize the risk of the disasters in the Andes mountains in which there are hazards such debris flows, rack-fall, subsidence and floods. The values considered were: the person as center, the pertinence, property sense and self-steem. The curricula six students modules named “The people of the mountains’? The Mountains ecosystem, the livig beings, The Planet earth, and the machines and the Pedagogical project in disaster prevention for the teachers. The curricula were validated la schools of Utica and Choachi (Cundinamarca department).